2018
DOI: 10.4103/jlp.jlp_144_17
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response markers in preeclampsia

Abstract: PURPOSE:Neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), platelet distribution width (PDW), red cell distribution width (RDW), mean platelet volume (MPV), and plateletcrit (PCT) are known as systemic inflammatory response markers. In this study, we aimed to evaluate changes in NLR, PLR, PDW, RDW, MPV, and PCT in preeclampsia (PE) and their use in predicting its severity.MATERIALS AND METHODS:This is a retrospective case–control study. The study comprised 64 control group (healthy pregnant fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 20 publications
1
28
1
3
Order By: Relevance
“…The association between NLR/PLR and preeclampsia produced mixed results in previous studies [11,12,13].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The association between NLR/PLR and preeclampsia produced mixed results in previous studies [11,12,13].…”
Section: Discussionmentioning
confidence: 90%
“…Cintesun et al, in 2018, did not find any statistically significant difference regarding NLR and PLR between 64 patients with preeclampsia and 66 women with healthy pregnancies in the third trimester [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also led to a search for novel useful markers similar to CRP. Recent studies have shown platelets to be the most important potential inflammatory candidates and changing values could be useful to demonstrate events of SI (2,30). Therefore, platelet-related parameters were analysed in this study in addition to CPR and ESR.…”
Section: A B C D E Dmentioning
confidence: 99%
“…Evaluation of the inflammatory condition may allow important predictions of the effectiveness of the surgical procedure and postoperative recovery (28). Recent studies have shown a significant relationship between platelets and inflammatory events in several diseases (2,17,23,30). Therefore, it can be considered that novel platelet-associated inflammation parameters (PAIP) such as Platelet Distribution Width (PDW), Mean Platelet Volume (MPV), Platelet-to-Lymphocyte Ratio (PLR) and Neutrophil-to-Lymphocyte Ratio (NLR) could provide information about inflammatory events.…”
mentioning
confidence: 99%